Collision Tumour of Squamous Cell Carcinoma and Malignant Melanoma in the Oral Cavity of a Dog. Issue 4 (May 2016) - Rodríguez, F.; Castro, P.; Ramírez, G.A.
Summary: A 7-year-old, male cocker spaniel was presented with a gingival proliferative lesion in the rostral maxilla and enlargement of the regional lymph node. Morphological and immunohistochemical analysis revealed a collision tumour composed of two malignant populations, epithelial and melanocytic, with metastasis of the neoplastic melanocytes to the regional lymph node. The epithelial component consisted of trabeculae and islands of well-differentiated squamous epithelium immunoreactive to cytokeratins. The melanocytic component had a varying degree of pigmentation of polygonal and spindle-shaped cells, growing in nests or densely packed aggregates and immunolabelled with S100, melanoma-associated antigen (melan A), neuron-specific enolase and vimentin antibodies. Protein markers involved in tumorigenesis or cell proliferation (i.e. COX-2, p53, c-kit and Ki67), were overexpressed by the neoplastic cells. To the authors' knowledge, this is the first description of an oral collision tumour involving malignant melanoma and squamous cell carcinoma in the dog.